Reseña bibliográfica - Plaja Viñas, Teresa (Comunitania. Revista Internacional de Trabajo Social y Ciencias Sociales, 2023)
Reseña del libro: Bundschuh, S., Freitas, M. J., Palacín Bartrolí, C and Žganec, N. ed. 2021. Ambivalences of Inclusion in Society and Social Work. Research-Based Reflections in Four European Countries. Springer